2011
DOI: 10.1097/phm.0b013e3182017269
|View full text |Cite
|
Sign up to set email alerts
|

Disability Attitudes in Health Care

Abstract: The new Disability Attitudes in Health Care scale developed in this study shows good internal consistency and criterion validity. Attitudes toward caring for patients with disability seem to be unrelated to the standard medical education curriculum or previous experience with disability. Specific educational experiences may be designed to engender more positive attitudes toward providing health care to this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…A number of these focus on particular providers' attitudes toward disability, such as the attitudes of health care workers (Chadd & Pangilinan, 2011), rehabilitation specialists (Dunn, 1996;Dunn & Mermis, 1992), dental professionals (Miller & Heil, 1976), and nurses (Gething, 1992). However, we have identified only one instrument addressing the attitudes of social workers toward disability.…”
mentioning
confidence: 99%
“…A number of these focus on particular providers' attitudes toward disability, such as the attitudes of health care workers (Chadd & Pangilinan, 2011), rehabilitation specialists (Dunn, 1996;Dunn & Mermis, 1992), dental professionals (Miller & Heil, 1976), and nurses (Gething, 1992). However, we have identified only one instrument addressing the attitudes of social workers toward disability.…”
mentioning
confidence: 99%
“…14,20,33,35,36 Tervo found that male medical students had more behavioral misconceptions about people with disabilities than did their female counterparts. He also found that female students were less likely to view special programs such as rehabilitation programs as too expensive.…”
Section: Discussionmentioning
confidence: 97%
“…33 Chadd also found that female medical students had more positive attitudes than male students did, and that male medical students had worse attitudes toward disability as compared with men in other allied health professions. 35 For the most part, in our curriculum, students encountered people with disabilities in educational or clinical settings where the special needs of this population were highlighted. Although this allowed the students to acquire focused experience working with people with disabilities, it may have also served to reinforce the perception that people with disabilities require and/or demand special treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Analysis of variance was used to evaluate the difference between the mean total scores of the 2 groups. Characteristics of the 2 groups were analyzed using the Pearson W 2 test of frequencies for binary variables and the Kruskal-Wallis W 2 test of frequencies for ordinal variables.…”
Section: Discussionmentioning
confidence: 99%
“…18 The purpose of this study was to assess the impact of a brief curricular intervention on students_ attitudes toward PWDs in the healthcare setting using the Disability Attitudes in Health Care (DAHC) scale. 19 Using the DAHC scale, the authors of this study sought to identify characteristics of medical students that correlated with more positive attitudes toward PWDs. The DAHC scale was given to the students by the Department of Rehabilitation Medicine to determine if the curricular intervention being created was effective and to guide improvements in the curriculum.…”
mentioning
confidence: 99%